Morpho-cultural, biochemical analysis and molecular characterization of pigment producing Cordyceps militaris - Kuamr, Satish; Kaundal, Kirti; Rao, Anil; Sharma, Shweta; Sharma, Ved Parkash (Mushroom Research, 2023)
The study was conducted to ascertain the cultural growth and nutritional content of the strain Cordyceps militaris cultivated in India. Abundant mycelial density and darkest orange pigment was observed in Potato dextrose agar which was followed by Oat meal agarand least was observed in Yeast agar medium.Inbioactive compounds, adenosine and cordycepin content was1.8 mg/g and 9.8 mg/g respectively. Additionally, proximate analysis of Cordyceps militaris contained proteins (32gm/100g) and carbohydrate (40mg/100g), dietary fiber (1.97g/100g), fat (0.23g/100g), sodium (46mg/100g, vitamin C (113mg/100g), total ash (7.82gm/100g),and saturated fatty acid (0.12g/100g) on dry weight basis.Heavy metal analysis showed lesser amount of Pb, Cd (<0.01 mg/kg) and Hg (<0.001 mg/kg).Microbiological testing was done, and staphylococcus and salmonella showed least effect on fruiting bodies of Cordyceps militaris. Molecular identification showed 99.83% similarity with Cordyceps militaris.The carotenoid and lycopene content were also estimated.SEM was done formicromorphological characteristics of conidia and conidiophore formation. Fruiting bodies was fully developed into orange club shaped structures after 45 days of inoculation.